PENGARUH PROMOSI DAN MUTASI JABATAN TERHADAP PRESTASI KERJA PEGAWAI PADA PENGADILAN NEGERI SIGLI - Husaini Abdullah (Universitas Jabal Ghafur, 2020)
This study aims to know and analyze the influence of Promotion and Position Mutation on Job Performance Employees in the District Court Sigli. Where the independent variables of Promotion, Job Mutation and Job Performance (Y) as dependen. The Population variable in this research is all employees of the District Court Sigli 45 employees . The entire population in the study were sampled in the study of 45 employees. Data collected in this study consisted of primary data and secondary data, both qualitative data and quantitative data and through questionnaires filled by respondents. Then the data obtained were analyzed by using multiple regression analysis . This analysis includes Normality Test, Multicolinearity Test, Heterokedasticity Test of Classic Assumption, Hypothesis Testing through F Test and T Test, and Determination Coefficient Analysis (R²). Based on the result of research, we get regression equation: Y = 1,171 + 0,358 X1 + 0,388 X2. The result of the above analysis can be concluded based on t test known that Positive Promotion Variables positively and significantly influence on employee performance at Sigli District Court. This is seen from the significant value (0,000) smaller than 0.05 and the value of thitung4.032> ttabel 1.682. Position Mutation variables positively and significantly influence on Employee Performance at Sigli District Court. This can be seen from the significant value (0.000) smaller than 0.05 and the value of tcount4.584> ttable1,682. Based on the calculation of the coefficient of determination (R2), indicating that the Adjusted R2 or the determinant of 0.715 means that 71.5% of Employee Performance factors can be explained by Position Promotion (X1) and Position Mutation (X2), while the remaining 28.5% can be explained by other factors not examined in this study. Keywords: Promotion, Job Mutation, Job Performance